If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5y + 4) + -1(-4y + -5) = 0 Reorder the terms: -1(4 + 5y) + -1(-4y + -5) = 0 (4 * -1 + 5y * -1) + -1(-4y + -5) = 0 (-4 + -5y) + -1(-4y + -5) = 0 Reorder the terms: -4 + -5y + -1(-5 + -4y) = 0 -4 + -5y + (-5 * -1 + -4y * -1) = 0 -4 + -5y + (5 + 4y) = 0 Reorder the terms: -4 + 5 + -5y + 4y = 0 Combine like terms: -4 + 5 = 1 1 + -5y + 4y = 0 Combine like terms: -5y + 4y = -1y 1 + -1y = 0 Solving 1 + -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 0 + -1 -1y = 0 + -1 Combine like terms: 0 + -1 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| p-27=-29 | | 8(4x-4)=4(8x+5) | | 2x^2-21x+27=0 | | 9+2m-4=7m+11-3m | | 0.1x+18.2=x-5.29 | | 86=(1..8c)+32 | | 3(3x-1.4)=6x-4.2 | | -(6y+1)-(-5y-5)=4 | | 9s+9s=162 | | 5(x+1.71)=4x | | x=x(x-6) | | 8(2x-3)=2(8x+5) | | 5+2x-2=6x+4-3x | | 4.4x-59=2.9x+4 | | 7.8=10x+1.6 | | 7p+2p=81 | | 6.6x+8-4.6x=6 | | 6z-4=38 | | -8.2x=73.8 | | 0.3x+0.1=-1.4 | | 9(x-6)+18=0 | | 5n=-10 | | 9(x-9.8)=4.5 | | 5x+8.87=2x+14 | | 14x+6-4=13x-2 | | 2.6m+6.98=-9.66 | | 4.6q-3.9-4.9q=-1.3q-1.6 | | 7V^3=112V | | m-37=-18 | | 7.9t+2.82=-55.64 | | -5x^2-14x+2=0 | | -5x^2+14x+2=0 |